Chapecó durante o Estado Novo (1937-1945): uma reflexão a partir dos conceitos de progresso, nacionalismo e fronteira - Bonsere, Kelvin Francisco (2020)
This paper proposes to problematize the resonances of the archetype of border expansion of capital applied in Chapecó in the delimited period of the Estado Novo, which was consolidated in the country between the years 1937 and 1945. This theme is the result of an opportunity to problematize and understand the current discourses in the region, which proclaim an idea of a city in progress, the fruit of a Europeanized colonization, which the statesmanship period promoted, seeking to create in the region its bastion of Brazilianness and ensure the borders of the country, in an action aligned with its nationalist policy. Thus, the transformation of Chapecó into a new pole of the capital in the western region of Santa Catarina, took place in a context of authoritarian ascension, and mainly persecution of the elements considered harmful to the inculcation of Brazilianity, formulated from the ideology of the March to the West, managed by the ideologists of the Estado Novo. In Chapecó, the elite formed by the first settlers and holders of the media vehicle written at Voz de Chapecó, sought to resinify the nationalist ideals in order to turn the migrant settlers of European descent into elements suitable for the retail project. For such work, the use of the journalistic source helped to understand the discourse emanating from this elite, congregated the official source that unveiled the links to concretize the discourse in reality.